PTEN Down‐Regulation Promotes β‐Oxidation to Fuel Hypertrophic Liver Growth After Hepatectomy in Mice. Issue 3 (20th July 2017) - Kachaylo, Ekaterina; Tschuor, Christoph; Calo, Nicolas; Borgeaud, Nathalie; Ungethüm, Udo; Limani, Perparim; Piguet, Anne‐Christine; Dufour, Jean‐Francois; Foti, Michelangelo; Graf, Rolf; Clavien, Pierre A.; Humar, Bostjan
Abstract : In regenerating liver, hepatocytes accumulate lipids before the major wave of parenchymal growth. This transient, regeneration‐associated steatosis (TRAS) is required for liver recovery, but its purpose is unclear. The tumor suppressor phosphatase and tensin homolog (PTEN) is a key inhibitor of the protein kinase B/mammalian target of rapamycin axis that regulates growth and metabolic adaptations after hepatectomy. In quiescent liver, PTEN causes pathological steatosis when lost, whereas its role in regenerating liver remains unknown. Here, we show that PTEN down‐regulation promotes liver growth in a TRAS‐dependent way. In wild‐type mice, PTEN reduction occurred after TRAS formation, persisted during its disappearance, and correlated with up‐regulated β‐oxidation at the expense of lipogenesis. Pharmacological modulation revealed an association of PTEN with TRAS turnover and hypertrophic liver growth. In liver‐specific Pten –/– mice shortly after induction of knockout, hypertrophic regeneration was accelerated and led to hepatomegaly. The resulting surplus liver mass was functional, as demonstrated by raised survival in a lethal model of resection‐induced liver failure. Indirect calorimetry revealed lipid oxidation as the primary energy source early after hepatectomy. The shift from glucose to lipid usage was pronounced in Pten –/– mice and correlated with the disappearance of TRAS. Partial inhibition of β‐oxidation led to persisting TRAS in Pten –/– mice and abrogated hypertrophic liver growth. PTEN down‐regulation may promote β‐oxidation through β‐catenin, whereas hypertrophy was dependent on mammalian target of rapamycin complex 1. Conclusion : PTEN down‐regulation after hepatectomy promotes the burning of TRAS‐derived lipids to fuel hypertrophic liver regeneration. Therefore, the anabolic function of PTEN deficiency in resting liver is transformed into catabolic activities upon tissue loss. These findings portray PTEN as a node coordinating liver growth with its energy demands and emphasize the need of lipids for regeneration. (Hepatology 2017;66:908–921).